A kiss of hammer and flame - De la Force, Amy (De la Force, Amy, Fated for Hael, 2025)
An immortal bound in darkness. A shattered empire at war. And a blacksmith whose heart could tip the scales of fate. When young blacksmith Cahra is commissioned to forge a sword, she uses her imagination to design its crest. But this symbol unwittingly invokes an age-old prophecy and awakens Hael - an immortal with the power to shape or shatter worlds - sealed away for hundreds of years in a chamber deep in Hael'stromia, the lost capital at the heart of a civil war between three kingdoms. Now hunted for the sword, Cahra must flee with the very stranger who commissioned it. But can she trust the handsome and charming noble, Terryl? On the run through the darkly magical Wilds, she is drawn ever closer to Hael, who visits and beguiles her in dreams. With tyrant kings vying to capture and wield him as a weapon, she alone stands between Hael and their deadly ambitions.